PHC1 maintains pluripotency by organizing genome-wide chromatin interactions of the Nanog locus - Li Chen (Nature Portfolio, 2021)
Phc1 is a subunit of the polycomb repressive complex 1 (PRC1), which represses gene expression during development. Here the authors show that Phc1 acts independently from PRC1 to activate Nanog transcription by stabilizing genome-wide chromatin interactions of the Nanog locus, and in turn stabilize pluripotency.